Landasan Manajemen Pendidikan Islam - H Mahmud (Pena Islam Jurnal Pendidikan Agama Islam, 2020)
The foundation of Islamic education management that is fundamental to the basis or principle that Islamic education management can be upright not easily collapsed due to the wind blowing ideology that appears now or in the future. The foundation of Islamic education management is of course based on the philosophy of life of Muslims and not based on the philosophy of life of a country or other ideology. Because the Islamic education management system can be implemented anywhere and anytime without being limited by space and time. The management of Islamic education is the art and science of managing, organizing Islamic education resources (human and other resources) in an Islamic way to achieve the goal of Islamic education effectively and efficiently. The foundation of Islamic education management includes: 1) Al-Qur'an, 2) as-Sunnah, 3) Al-Kaun, and 4) Ijtihad.